Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1085/jgp.202112924
|View full text |Cite
|
Sign up to set email alerts
|

The epithelial potassium channel Kir7.1 is stimulated by progesterone

Abstract: The choroid plexus (CP) epithelium secretes cerebrospinal fluid and plays an important role in healthy homeostasis of the brain. CP function can be influenced by sex steroid hormones; however, the precise molecular mechanism of such regulation is not well understood. Here, using whole-cell patch-clamp recordings from male and female murine CP cells, we show that application of progesterone resulted in specific and strong potentiation of the inwardly rectifying potassium channel Kir7.1, an essential protein tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 41 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…Recently, we reported that murine Kir7.1 expressed in the choroid plexus and retinal pigment epithelia is potently and specifically activated by progesterone (19,20) and that such activation is independent of G-protein regulation (20). This finding led us to compare the properties of human and murine Kir7.1 to verify whether human Kir7.1 can be regulated by progesterone in the similar manner.…”
Section: Results Kir 71 Is Expressed In Myometrial Smooth Muscle and ...mentioning
confidence: 99%
“…Recently, we reported that murine Kir7.1 expressed in the choroid plexus and retinal pigment epithelia is potently and specifically activated by progesterone (19,20) and that such activation is independent of G-protein regulation (20). This finding led us to compare the properties of human and murine Kir7.1 to verify whether human Kir7.1 can be regulated by progesterone in the similar manner.…”
Section: Results Kir 71 Is Expressed In Myometrial Smooth Muscle and ...mentioning
confidence: 99%
“…These receptors include a class of G-protein coupled receptors (GPCRs) called membrane progesterone receptors (mPRs) that activate intracellular signaling pathways akin to other GPCRs and have neuroprotective effects ( Thomas and Pang, 2020 ), and PGRMC1 (PROG receptor membrane component 1), receptors that activate cytochrome P450 enzymes, affect lipid metabolism and promote cell survival ( Bassani et al, 2022 ; Ghoumari et al, 2020 ; Gonzalez et al, 2020 ). PROG was recently shown to be a PAM of the voltage-gated potassium channel Kir7.1 in epithelial cells of the choroid plexus ( Bjorkgren et al, 2022 ). While it is unclear whether PROG directly modulates GABA A Rs, it is certain that some of its metabolites (e. g. AlloP and others) are highly effective and direct acting PAMs.…”
Section: Progesteronementioning
confidence: 99%
“…The senior Cranefield Award, for someone at the start of their independent research career, has been awarded to Polina Lishko, from the University of California, Berkeley. Her work investigated the mechanism by which sex steroid hormones influence the choroid plexus and identified a role for progesterone in increasing an inwardly rectifying potassium current, Kir7.1 ( Björkgren et al, 2021 ).…”
mentioning
confidence: 99%